Study on occurrence law of sulfur in high-sulfur coal with different particle sizes and densities - Yulong YANG; Fei GAO; Yunming ZHANG (Meikuang Anquan)
To investigate the state of sulfur in different particle sizes and density fractions of high-sulfur coal, the Ciyaogou high-sulfur coal was divided into particle size and density fractions according to the screening method and flotation method. XPS (X-ray photoelectron spectroscopy) and FTIR (Fourier transform infrared spectrometer) were used to test the elements and groups, and analyze the categories of the sulfur forms and the sulfur functional groups that changed with particle size and density. The trace elements in each fraction of Ciyaogou high-sulfur coal were tested using XRF (X-ray fluorescence spectroscopy), and the correlation between sulfur elements and trace elements was studied using the Pearson correlation coefficient method. The main form sulfur in Ciyaogou coal is mercaptan, mass fraction is more than 45%, followed by thiophene and sulfate, mass fraction is more than 15%, and pyrite, sulfone and sulfoxide are less, mass fraction is less than 10%, indicating that sulfur in Ciyaogou coal mainly exists in the form of organic sulfur. The relative content of C-SH in sulfur-containing functional groups was the highest, with the peak area accounting for 9%-14%. The content of R-SO-R' and R-SO2-R' was less, with the peak area all below 4%. As the particle size increased, the total sulfur content decreased, and the concentration of sulfides and thiophenes increased, while the concentration of sulfates decreased. The content of sulfoxides and sulfones remains relatively unchanged. With increasing density, the total sulfur content in coal increased, and the content of sulfides and thiophenes decreased, while the sulfate content increased. The content of sulfoxides and sulfones showed no significant change, indicating that organic sulfur mainly occurred in larger particles and low-density coal, while inorganic sulfur tends to occur in smaller particles and high-density coal. Analysis of Pearson correlation coefficients between inorganic and organic sulfur and other trace elements revealed that inorganic sulfur exhibited a strong positive correlation with elements such as Fe and K, while organic sulfur demonstrated a strong negative correlation with these elements. This suggested that the sulfur in pyrite or sulfates was associated with these elements in coal, while organic sulfur had a lower affinity for such elements.